Comparison of mitral annulus geometry between patients with ischemic and non-ischemic functional mitral regurgitation: implications for transcatheter mitral valve implantation - Aruta, Patrizia (Cardiovasc Ultrasound, 2018)
BACKGROUND: Transcatheter mitral valve replacement (TMVR) is a new therapeutic option for high surgical risk patients with mitral regurgitation (MR). Mitral valve (MV) geometry quantification is of paramount importance for success of the procedure and transthoracic 3D echocardiography represents a useful screening tool. Accordingly, we sought to asses MV geometry in patients with functional MR (FMR) that would potentially benefit of TMVR, focusing on the comparison of mitral annulus (MA) geometry between patients with ischemic (IMR) and non ischemic mitral regurgitation (nIMR). METHODS: We retrospectively selected 94 patients with severe FMR: 41 (43,6%) with IMR and 53 (56,4%) with nIMR. 3D MA analysis was performed on dedicated transthoracic 3D data sets using a new, commercially-available software package in two moments of the cardiac cycle (early-diastole and mid-systole). We measured MA dimension and geometry parameters, left atrial and left ventricular volumes. RESULTS: Maximum (MA area 10.7 ± 2.5 cm(2) vs 11.6 ± 2.7 cm(2), p > 0.05) and the best fit plane MA area (9.9 ± 2.3 cm(2) vs 10.7 ± 2.5 cm(2), p > 0.05, respectively) were similar between IMR and nIMR. nIMR patients showed larger mid-systolic 3D area (9.8 ± 2.3 cm(2) vs 10.8 ± 2.7 cm(2), p < 0.05) and perimeter (11.2 ± 1.3 cm vs 11.8 ± 1.5 cm, p < 0.05) with longer and larger leaflets, and wider aorto-mitral angle (135 ± 10° vs 141 ± 11°, p < 0.05). Conversely, the area of MA at the best fit plane did not differ between IMR and nIMR patients (9 ± 1.1 cm(2) vs 9.9 ± 1.5 cm(2), p > 0.05). CONCLUSIONS: Patients with ischemic and non-ischemic etiology of FMR have similar maximum dimension, yet systolic differences between the two groups should be taken into account to tailor prosthesis’s selection. TRIAL REGISTRATION: N.A.